KERAGAAN DAN PERAN MODAL VENTURA TERHADAP PERIKANAN TANGKAP DI KOTA TEGAL, JAWA TENGAH - Ach. Nafani Manaf; John Haluan; Akhmad Fauzi; Fatchudin Fatchudin (Buletin PSP, 2009)
Nowadays,venture capital is not  known on the field of marine and fisheries, while this sector has a problem in capital needed.  Challenges of capital needed  have became a classical problem on fisheries sector, so it requires a comprehensive solution by all parties.  The existence of venture capital on the one hand who actually provide the opportunity is big enough to bridge and help solve the problem.  But on the other hand, until this time there is no model for the appropriate use of venture capital in the fishery.  The goal of this research is to analyze the role of venture capital funding in the fishery, to analyze the impact/influence of the venture capital  fishery and determine the development of policy scenarios for the development of venture capital fisheries.  This research is conducted in the Tegal District because this area has a lot of fishermen who receive assistance from the venture capital PT Facilities Central Java Ventura. approaches of this reseach are descriptive analysis, regression analysisand Data Envelopment Analysis (DEA).  The results of  this research are venture capital have positif or significant influence to the performance of fisheries sector in Tegal District if its  operated appropriate with early criterias or terms of venture capital ditribution and it is need specific criterias terms in venture capital credit distribution, such as ship lifespan, fisherman experiences and capital quantity that distributed.   Key words: capture fisheries, performance, Tegal District, venture capital